2021
DOI: 10.1111/add.15327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alcohol label designs with different pictorial representations of alcohol content and health warnings on knowledge and understanding of low‐risk drinking guidelines: a randomized controlled trial

Abstract: Background and aims The UK low‐risk drinking guidelines (LRDG) recommend not regularly drinking more than 14 units of alcohol per week. We tested the effect of different pictorial representations of alcohol content, some with a health warning, on knowledge of the LRDG and understanding of how many drinks it equates to. Design Parallel randomized controlled trial. Setting On‐line, 25 January–1 February 2019. Participants Participants (n = 7516) were English, aged over 18 years and drink alcohol. Interventions T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…In total, we identified 27 papers that fit our inclusion criteria (see Appendix A for PRISMA diagram) [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. One paper reported on two studies using different methodologies to study the same variables [ 50 ], and four papers reported on different aspects of one intervention [ 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, we identified 27 papers that fit our inclusion criteria (see Appendix A for PRISMA diagram) [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. One paper reported on two studies using different methodologies to study the same variables [ 50 ], and four papers reported on different aspects of one intervention [ 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of study aims and studied independent variables, five papers (19%) compared only new or enhanced labels with no or regular labels [ 51 , 52 , 53 , 54 , 63 ]. Focusing on label content, eight papers (30%) compared text-only labels with text and image labels [ 55 , 56 , 61 , 62 , 64 , 65 , 66 , 67 ], twelve studies (44%) compared text message characteristics (e.g., content, specificity, framing, source, use of causal language) [ 57 , 58 , 59 , 60 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ] and three (11%) compared image characteristics [ 57 , 66 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations